Fluorescent nanoplastics increase the toxic effects of Graphene oxide nanoparticles in freshwater algae Scenedesmus obliquus - Soupam Das; Sampriti Giri; Janmey Shah; Amitava Mukherjee (Toxicology Reports)
The increased usage of Graphene oxide (GO) in various industrial applications led to their entry into freshwater systems. Other secondary contaminants like nanoplastics (NPs) often co-exist with GO in the environment. This study examines the possible role of fluorescent nanoplastics (FNPs) in modifying the toxic effects of GO on freshwater algae Scenedesmus obliquus. Selected concentrations of GO (0.1, 1, and 10 mg L−1) were combined with a fixed concentration of FNPs (1 mg L−1) to perform combinational toxicity tests on algae. FNPs significantly enhanced the toxic effects of GO in the mixtures in comparison with the pristine GO. In addition to the cytotoxic effects, oxidative stress parameters like total ROS generation and malondialdehyde (MDA) production also increased in the case of the combined pollutants. The antioxidant enzymatic activities like catalase (CAT) and superoxide dismutase (SOD) in the cells were also assessed. Algal exposure to the pristine pollutants and their mixture led to a notable decrease in photosynthetic activities in the cells, with the mixed pollutants aggravating the loss of activity. The interactive toxic effects of the contaminants when present in mixtures were evaluated using Abbotts' Independent action modelling. Furthermore, optical microscopic images revealed the morphological changes in the algal cells after exposure to the contaminants both in the pristine and combined forms.